INDUSTRIAL TRIALS OF THE REFINING TECHNOLOGY FOR LONG-TERM STORED SUNFLOWER OIL - Erkayeva, Nodira; Ahmedov, Azimjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article discusses the results of a refining technology for processing long-stored sunflower oil. After adding a filtering agent in the amount of 0.1-0.3% to the same oil samples, an increase in the oil filtration rate from 0.42 to 1.63 kg s/m2 was achieved during filtration. Simultaneously, the color of the oil decreased from 14 mgJ to 8 mgJ. It can be observed that the acid value of the oil decreased from 0.17 to 0.15 mg KOH/g, while the yield increased from 98.1% to 99.2%. The results indicate that the developed technology and filtering agent are highly effective in processing oils that have been stored for a long time.